Classification of transport systems taking into account diagnostic approach - Горяинов, Алексей Николаевич (Eastern-European Journal of Enterprise Technologies, 2012)
The questions of formation of approaches to transport systems research are considered. Lacks of existing definitions and classifications of transport sphere are allocated. The approach to classification of systems of transport as technological systems is offered